Cross-cultural adaptation and psychometric validation of the Finnish version of the Expanded Prostate Cancer Index Composite-26 for patients with localised prostate cancer - Ettala, Otto; Bergroth, Robin; Riikonen, Jarno; Boström, Peter; Koskimäki, Juha; Kuisma, Jani; Rannikko, Antti; Vaarala, Markku; Sanda, Martin G; Santti, Henrikki (Medical Journals Sweden AB, 2026)
Objective: The study aimed to culturally adapt the Expanded Prostate Cancer Composite-26 (EPIC-26) questionnaire to Finnish and evaluate its usability in routine clinical practice in Finland.
Material and methods: We translated the EPIC-26 questionnaire into Finnish, reviewed it, back-translated it into English, and reviewed it again. We evaluated the questionnaire in four high-volume university hospitals in Finland. The study included 220 Finnish-speaking patients with untreated, newly diagnosed non-metastatic prostate cancer. Patients completed the EPIC-26 twice before treatment and twice 6 months after treatment. We assessed internal consistency, test-retest reliability, sensitivity to change, and unanswered questions.
Results: The mean age of the patients was 68 years, with 69% diagnosed with low- or intermediate-risk prostate cancer according to the D’Amico classification. The most common treatment was radical prostatectomy (36%), followed by radiation therapy (31%) and active surveillance (25%). The minimum score, i.e. the worst assessment, was observed most frequently in the sexual domain (8%), while the maximum score was in the bowel domain (47%). Irritation/obstruction and hormonal domains showed low internal consistency due to the questions regarding haematuria and breast problems. Patients who underwent radical prostatectomy or radiation therapy had statistically significant changes between pre- and post-treatment scores. Most men (72%) completed the questionnaire. Older patients were more prone to leave questions unanswered, particularly questions with multiple items (odds ratio 0.39; 95% confidence interval 0.20–0.80).
Conclusions: The Finnish version of the EPIC-26 questionnaire can be used in clinical practice. Completing the questionnaire may be more difficult for older patients.